Type 2 Gaucher disease among in Ashkenazi Jews - Aviner, Shraga (2009)
Patients with Gaucher disease (GD) are typicslly divided into 3 types based on the presence and rate of progression of the neurologic manifestations. While type 1 GD has a strong predilection in the Jewish Ashkenazi population, both other types lack such a propensity. We report the occuranve of type 2 GD in six pregnancies in three Jewish families in Israel, and also review seven additional cases of type 2 GD in Ashkenazi Jewish families patients reported in the literature. Geneotypic analysis of probands from the three Israeli families demonstrate that all carried two heterozygous glucocerebrosidase mutations. We conclude that type 2 GD in Ashkenazi Jews is extremely rare, but that phenotypically it does not differ significantly from this form of thee disease in other ethnic groups. The recurrence of multiple cases in families emphasizes the need for proper diagnosis and genetic counseling regarding type 2 GD among Ashkenazi Jews